Social Welfare In India - Planning Commission (Planning Commission, 1955)
The following paper seeks to present the historical background of the development of social work in India. The words historical background are used deliberately and are intended to distinguish it from a history of social work in India. What has been attempted is the presentation of the thought of some of the more important thinkers and social reformers of the nineteenth and twentieth centuries with a view to showing the relation between the trends of thought and the development of social work. There is, therefore, no effort to recount in any detail the actual occurrence of events in the field of social work and social reform.
Planning Commission
Planning Commission